Assessment of awareness of orthodontic emergencies and psychosocial wellbeing of patients during novel coronavirus pandemic through teledentistry - Kanwal Zulfiqar, Kanwal Zulfiqar (Journal of Rawalpindi Medical College, 2022)
Introduction: At the end of December 2019, the novel coronavirus began to spread in central China and soon became a pandemic. Unfortunately, all elective dental treatments including orthodontic visits were postponed and patients could not be counselled on how to manage orthodontic emergencies that they could encounter at home. Teledentistry can play a major role in providing instructions to patients during quarantine. Objective: The study aimed to assess the awareness of orthodontic patients regarding the management of orthodontic emergencies and their psychosocial well-being during the novel coronavirus pandemic through Teledentistry. Materials and Methods: A questionnaire-based study was conducted on two groups during the lockdown period in which their anxiety, psychological status, and their ability to manage orthodontic emergencies at home during the COVID-19 pandemic lockdown were assessed through teledentistry. Results: A total of 170 patients participated in our study, Independent sample t-test was used to compare the means of the group’s control and experimental. Statistically, a significant difference was determined between the two groups regarding their psychosocial well-being (social media embarrassment p=0.049, awareness of how to manage orthodontic emergencies p=0.00). The participants displayed a better understanding of how to deal with orthodontic emergencies at home after having instructions. 48.2% of the patients selected voice call as a preferred mode of instruction for managing orthodontic emergencies at home. Conclusion: Experimental group of patients was more aware of how to manage orthodontic emergencies and they were less anxious. Teledentistry has proven to be an important tool for providing instructions to anxious patients as well as reducing the spread of coronavirus due to lack of contact. Voice call was the preferred mode of instruction. Keywords: Anxiety, COVID-19, Orthodontic emergencies, Tele-dentistry.